(3eMehO GdebGUO Ydi LGeY GdYbGFOs - (3eMeO GdCejf YHO GdhgGH GdadGdjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO ajbhd CMhL GdNdb Ydi GdEWdGb HYah QHg GdNdGb eMeO GdCejf Hf YHO GdhgGH GdadGdi hSejJg eMehO GdebGUO Ydi LGeY GdYbGFO s
(3BNQgG (B:s
(3Gdegjef Ci HGddg agh ef CSeGFg JYGdi heYfGg GdeQGbH ddGTjGA GdedGMX dgG YdG Yf cd fbU YdhkG cHjQkG hgPg GdcdeI GdJi NJeJ HgG gPG GdfXe dgG ef GdaVd hGdahGFO eGdGjONd JMJ MUQ abO KHJ hUM CfgG cfR ef cfhR GdLfI hcGfJ OhGA ef JSY hJSYjf OGA s
(3GdfSNI HgG MhGTs
(3fSNI HgG BKGQ QWhHI JSHHJ ai JBcd HYV CWQGagG hVGYJ HYV cdeGJgGs
(3Ydi MhGTjgG TQhM hJUMjMGJ s
(3hai cd UaMI ef CYdGgG cJHJ Gddge Udi Ydi GdfHi GdMHjH s
(3cJHJ YfGhjfgG HGdMHQ GdCMeQ s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds